2022
DOI: 10.3389/fimmu.2022.976996
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analyses of classical protein tyrosine phosphatases and phosphatase-targeted therapy in cancer

Abstract: Protein tyrosine phosphatases function in dephosphorylating target proteins to regulate signaling pathways that control a broad spectrum of fundamental physiological and pathological processes. Detailed knowledge concerning the roles of classical PTPs in human cancer merits in-depth investigation. We comprehensively analyzed the regulatory mechanisms and clinical relevance of classical PTPs in more than 9000 tumor patients across 33 types of cancer. The independent datasets and functional experiments were empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Gene expressing matrix and area under the dosage response curve of glioma cell lines were collected from the GDSC database [ 35 , 36 ]. Correlation coefficient |Rs| > 0.25 and FDR < 0.05 were employed to further analysis [ 37 ]. In addition, previously conducted studies were used to obtain imputed tumor response data for 138 anti-cancer drugs, which were subsequently used to assess treatment response for GBM patients [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Gene expressing matrix and area under the dosage response curve of glioma cell lines were collected from the GDSC database [ 35 , 36 ]. Correlation coefficient |Rs| > 0.25 and FDR < 0.05 were employed to further analysis [ 37 ]. In addition, previously conducted studies were used to obtain imputed tumor response data for 138 anti-cancer drugs, which were subsequently used to assess treatment response for GBM patients [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…A study also demonstrated that PTPN18 promotes endometrial cancer cell line proliferation and metastasis but inhibits their apoptosis [11]. We previously performed the pan-cancer analysis of classical protein tyrosine phosphatases [12] and confirmed that PTPN18 can inhibit breast cancer metastasis [13]. However, the potential functions and mechanisms of PTPN18 in glioblastoma remain unclear.…”
Section: Introductionmentioning
confidence: 92%
“…Together, kinases and PTPs guard a balance in innumerable cell signaling pathways. Loss of this balance has been linked to a plethora of human diseases, including cancer (Hendriks et al, 2013;Tautz et al, 2013;Tonks, 2006; T. Wang et al, 2022).…”
Section: Table Of Contentsmentioning
confidence: 99%